TLX1/HOX11-mediated disruption of primary thymocyte differentiation prior to the CD4(+)CD8(+) double-positive stage - Owens, Bronwyn M. (2006)
The TLX1/HOX11 homeobox gene is frequently activated in T-cell acute lymphoblastic leukemia (T-ALL) by the t(10;14)(q24;q11) and t(7;10)(q35;q24) chromosomal translocations or by as yet unknown transcriptional mechanisms in the absence of 10q24 cytogenetic abnormalities. Almost all TLX1(+) T-ALLs exhibit a CD4(+)CD8(+) double-positive (DP) phenotype. To investigate the role of TLX1 as an initiating oncogene in T-ALL pathogenesis, we assessed the consequences of retroviral vector-directed TLX1 expression during the differentiation of murine and human thymocytes in fetal thymic organ cultures. Interestingly, enforced expression of TLX1 disrupted the differentiation of murine fetal liver precursors and human cord blood CD34(+) stem/progenitor cells prior to the DP thymocyte stage. Although differentiation arrest was associated with an increased percentage of apoptotic thymocytes, it could only be partially bypassed by coexpression of transgenic BCL2. Mutation of the invariant asparagine residue at position 51 of the homeodomain – which is required for efficient DNA binding – released the block, consistent with the notion that TLX1 inhibits thymocyte differentiation and promotes T-cell oncogenesis by functioning as a transcription factor. The relevance of these findings is discussed in the context of activating NOTCH1 mutations and the other genetic lesions implicated in the multistep transformation process of TLX1(+) T-ALL.